Peran Kelompok Tani Pada Petani Kelapa Sawit Swadaya di Kecamatan Subah - Fatimah, Nur Juwita; Novira Kusrini; Dewi Kurniati (Jurnal Ekonomi Pertanian dan Agribisnis, 2026)
Farmer groups are formed with the aim of further improving and developing the capabilities of members and their families. Farmer groups themselves are a form of farmer association that can be used as a place for extension activities. Extension activities through a group approach are intended to encourage the formation of farmer institutions that are able to build synergy between farmers and between farmer groups in order to achieve business efficiency. This study aims to determine the role of independent oil palm farmer groups in Subah District. This research was conducted from January to July in Subah District. The population in this study was 5,276 farmer members consisting of 13 villages. With a sample of 44 farmers, the selected sampling method was using the Slovin formula. The analytical method used was quantitative descriptive analysis by calculating the analysis of the role of independent oil palm farmer groups according to their functions, namely learning classes, cooperation platforms, production units measured using the Likert method. The results of the study showed that the role of farmer groups in Subah District in carrying out their roles as learning classes was classified as high at 77.3%, as cooperation platforms was classified as high at 86.4%, and as production units was classified as high at 72.7%